2017
DOI: 10.1016/j.pmedr.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preventive online mindfulness interventions on stress and mindfulness: A meta-analysis of randomized controlled trials

Abstract: Empirical evidence suggested that mind-body interventions can be effectively delivered online. This study aimed to examine whether preventive online mindfulness interventions (POMI) for non-clinical populations improve short- and long-term outcomes for perceived-stress (primary) and mindfulness (secondary). Systematic search of four electronic databases, manuscript reference lists, and journal content lists was conducted in 2016, using 21 search-terms. Eight randomized controlled trials (RCTs) evaluating effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
98
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 54 publications
11
98
0
2
Order By: Relevance
“…The significant moderate effect (g=0.54) on stress reduction is comparable to the findings of previous research conducted in the general population (16). The omission of two outliers (71,70) decreased the effect (from g=0.54 to g=0.44), in accordance with the results of previous meta-analyses in the general population (14,15). Community recruitment significantly enhanced the treatment effect (g=0.79), while workplace recruitment decreased the intervention effect.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The significant moderate effect (g=0.54) on stress reduction is comparable to the findings of previous research conducted in the general population (16). The omission of two outliers (71,70) decreased the effect (from g=0.54 to g=0.44), in accordance with the results of previous meta-analyses in the general population (14,15). Community recruitment significantly enhanced the treatment effect (g=0.79), while workplace recruitment decreased the intervention effect.…”
Section: Discussionsupporting
confidence: 88%
“…In another meta-analysis, Heber et al (14) reported a small effect size for stress symptoms (Cohen's d=0.43, noted as "d" hereafter). Similar results were found by Jayawardene et al (15) in their meta-analysis of the effectiveness of online mindfulness interventions, who found a small treatment effect (g=0.42), as well as by Spijkerman et al (16), who found a moderate effect size (g=0.51). Moderateto-large effect sizes (0.66<g<0.83) were also found for internet-based interventions for post-traumatic stress (17).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…A recent meta-analysis examining the impact of online MBIs in preventive medicine found moderate to large effects in perceived stress among non-clinical samples of volunteers. 33 Identification of the modules of the training that were more impactful may also assist in developing more intensive materials in content areas found to be most beneficial. As stress levels were measured only pre and post intervention, changes in stress in response to specific modules cannot be determined in this study and should be investigated in future research.…”
Section: Workplacementioning
confidence: 99%
“…In contrast, 6 weeks of an online intervention experiment 22 has revealed that Headspace, which is a healthcare app for mindfulness by guided 23 meditation, has relatively small effects on mindfulness [79]. The outcome contradicts the 24 results of previous randomized controlled trials for the app [49]. Because of such 25 contradictions, there is a need for a reliable mechanism to identify validated digital 26 health apps [69].…”
mentioning
confidence: 99%